Chinese Muslim Community Development in Contemporary Indonesia: Experiences of PITI in East Java - Mahfud, Choirul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
This article explores the development of an Indonesia’s Chinese Muslim community, which continues to be performed through various ways, media and development program strategies. The article focuses to delve the experiences of the Chinese Muslim Association of Indonesia (PITI) in East Java as an example of best practices in the development of a Muslim minority community. This community has empowered young generation of Chinese Muslims and has conducted a program which develops a synergy with Chinese non-Muslim in order to guide Mu’allaf (converts) especially in Cheng Hoo Mosque, the first Chinese mosques that was built in Surabaya. This Chinese-architecture mosque is not only as a new icon of religious tourism, but also as a symbol of openness, and multiculturalism in Indonesia. The development of this Chinese Muslim community has also involved women participation in a hijab fashion show contest, as well as annual international program for Chinese ulama and Muslim in Indonesia. This article also discusses the development of Chinese-based Islamic education institutions both schools and Islamic boarding schools (pesantren).